2016
DOI: 10.5194/isprsarchives-xli-b7-803-2016
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Multitemporal Tandem-X Derived Crop Surface Models for Maize Growth Monitoring

Abstract: ABSTRACT:In this study, first results of retrieving plant heights of maize fields from multitemporal TanDEM-X images are shown. Three TanDEM-X dual polarization spotlight acquisitions were taken over a rural area in Germany in the growing season 2014. By interferometric processing, digital terrain models (DTM) were derived for each date with 5 m resolution. From the data of the first acquisition (June 1st) taken before planting, a DTM of the bare ground is generated. The data of the following acquisition dates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…However, classification accuracy could be improved by using the different heights of maize and sugar beet at the end of the growing season. Hütt, Tilly, et al (2016) showed how the height of maize plants could be measured using SAR data from the TerraSAR-X Add-on for Digital Elevation Measurements (TanDEM-X).…”
Section: Discussionmentioning
confidence: 99%
“…However, classification accuracy could be improved by using the different heights of maize and sugar beet at the end of the growing season. Hütt, Tilly, et al (2016) showed how the height of maize plants could be measured using SAR data from the TerraSAR-X Add-on for Digital Elevation Measurements (TanDEM-X).…”
Section: Discussionmentioning
confidence: 99%